2021
DOI: 10.1093/jac/dkab172
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of antibiotics in the community, European Union/European Economic Area, 1997–2017

Abstract: Objectives Data on antibiotic consumption in the community were collected from 30 EU/EEA countries over two decades. This article reviews temporal trends, seasonal variation, presence of change-points and changes in the composition of the main antibiotic groups. Methods For the period 1997–2017, data on consumption of antibiotics, i.e. antibacterials for systemic use (ATC group J01), in the community, aggregated at the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 10 publications
(10 reference statements)
4
31
1
Order By: Relevance
“…Several other studies have described the differences in numbers, types and appropriateness of prescribed antibiotics between European countries. 1,3,6,7,19,30,31 The prescribing proportion in our PPAS were not always congruent with the ranking in ECDC reports 6,7 in which, for example, the Netherlands ranks lowest and Belgium considerably higher. However, overall antibiotic use is not only determined by the prescribing proportion, but also by the number of patients that yearly present to a GP, the denominator.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 81%
See 2 more Smart Citations
“…Several other studies have described the differences in numbers, types and appropriateness of prescribed antibiotics between European countries. 1,3,6,7,19,30,31 The prescribing proportion in our PPAS were not always congruent with the ranking in ECDC reports 6,7 in which, for example, the Netherlands ranks lowest and Belgium considerably higher. However, overall antibiotic use is not only determined by the prescribing proportion, but also by the number of patients that yearly present to a GP, the denominator.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 81%
“…This prospective 18-country audit of nearly 5,000 primary care consultations for RTI confirms considerable variation in both the proportion and the class of antibiotics prescribed. 6,7 There was also considerable variation in clinical assessments, POC and laboratory/hospital-based testing, and in non-antibiotic prescriptions. However, GPs consistently expressed a high level of confidence in their decision whether or not to prescribe antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that the consumption of antibacterials for systemic use in the primary care sector fell by 31.29% in Slovakia between 2011 and 2020. An international study by Bruyndonckx et al [16] describes trends in 30 EU/EEA countries, including Slovakia, of antibiotic consumption for the primary care sector and shows a decrease in Slovakia consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Globally, between the years 2000-2015, 42.3 billion DDD were consumed by humans and the antibiotics consumption rate increased 39%, being higher in high-income countries (Klein et al, 2018), with amoxicillin and amoxicillin/clavulanic acid being the most frequently consumed antibiotics in most countries (Aldeyab et al, 2020). Within the European Union, the antibiotics more consumed are the ones from the group of β-Lactam antibacterial molecules and penicillins (42.3%) and the general consumption pattern has not significantly change in the period 1997-2017 (Bruyndonckx et al, 2021). The country raking of antibiotic consumption in Europe is led by Greece, with Cyprus and Spain in second and third place, respectively (Bruyndonckx et al, 2021).…”
Section: Introductionmentioning
confidence: 99%